2019
DOI: 10.5204/ssj.v10i2.1293
|View full text |Cite
|
Sign up to set email alerts
|

The benefits of good tutor-student relationships in the first year

Abstract: Teacher-student relationships (TSR) are an important influence on the student experience at university. Existing research, predominantly with lecturers, highlights that these relationships have academic and affective dimensions. Studies demonstrate good TSR increase student motivation, engagement, and learning. The current study adds a student voice to this topic, focussing on their views of tutoring staff, who undertake much of the face-to-face teaching in universities. The qualitative study followed 19 stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…The findings also illustrate how easier communication with staff and other students fostered engagement via the pathways to engagement. An increased sense of belonging, to the course itself and the wider discipline, was most evident, aligning with other studies which have found that interaction and relationships foster belonging (Kahu and Picton, 2019;Maunder, 2018;Picton et al, 2017). Our findings support McInnerney and Roberts (2004) who argue that greater use of synchronous communication tools is necessary to effectively build community in online spaces.…”
Section: Student Engagementsupporting
confidence: 90%
“…The findings also illustrate how easier communication with staff and other students fostered engagement via the pathways to engagement. An increased sense of belonging, to the course itself and the wider discipline, was most evident, aligning with other studies which have found that interaction and relationships foster belonging (Kahu and Picton, 2019;Maunder, 2018;Picton et al, 2017). Our findings support McInnerney and Roberts (2004) who argue that greater use of synchronous communication tools is necessary to effectively build community in online spaces.…”
Section: Student Engagementsupporting
confidence: 90%
“…Not surprisingly this sense of approachability was most apparent when cohorts and class sizes were small but when the class sizes grew students felt more alone and struggled to find support within the academic maze. These findings resonate with those of Kahu and Picton (2019), who identified that the good tutor supported student engagement and fostered a stronger sense of belonging.…”
Section: Confidence Cultural Capital and Agencysupporting
confidence: 85%
“…In many universities, while students have access to lecture recordings ( Dona et al, 2017 ), it is the face-to-face tutorials, workshops, practicals and studios that facilitate more fruitful opportunities via real-time discussions with educators, and which strengthen and contextualise students' learning and application of content and concepts ( Fang & O'Toole, 2023 ; Kahu & Picton, 2019 ; Senali et al, 2022 ). Face-to-face tutorials also facilitate interactions among students where they learn experientially from each other and together, participating in conversations and designing and resourcing group work ( Topping et al, 2017 ).…”
Section: Discussion and Future Research Directionsmentioning
confidence: 99%